Impact of Capital Structure on Profitability of Dabur Nepal Private Limited - Shrestha, Sanjay (Journal of Economics and Management, 2023)
These studies investigate the Impact of capital structure and the Profitability of Dabur Nepal Private Limited. Data analysis was complete using descriptive statistics, Pearson correlation, regression analysis, and t-test. The secondary data used to analyze one (1) sample size, out of ten which, has been found to be covering the period 2013-2022 of private multinational manufacturing companies in Nepal. The capital structure represents the variables of the Debt - Equity Ratio (DER), Debt to Capital Ratio (DCR), Debt to Total Assets Ratio (DTAR), Equity to Total Assets Ratio (ETAR), Short-term Liability to Total Assets ratio (SLTAR) and the profitability including Return on Assets (ROA). The findings of the study have a R square value of 0.537, meaning that 53.7% of the variation in the dependent variable is explained by the independent variables while 46.3% is explained by other variables outside the model and also showed that there is a lower positive correlation between the dependent variable and the set of independent variables. The result showed that there is an insignificant impact of DER, DCR, DTA, ETA, and SLTA on ROE of Dabur Nepal Pvt. Ltd.